Water Quality Monitoring of Biological and Chemical Pollutants into the Wakkerstroom Wetland - Klinkert, Celine (University of the Witwatersrand, Johannesburg, 2024)
Wetlands are among the most important ecosystems in the world due to the array of ecosystem services that they provide, such as flood attenuation, ground water restoration, water filtration and pollutant removal, climate change regulation and reducing erosion. The Wakkerstroom wetland in the Mpumalanga Province South Africa, plays a major role in improving downstream water quality. The wetland is threatened due to excess nutrient loading and microbiological contaminants entering the water column from a sewage ground runoff and a malfunctioning wastewater treatment plant. This study aims to determine the water quality and nutrient removal from the wetland by assessing chemical parameters and coliform and E.coli contamination as faecal indicators. Eight sampling sites were chosen along the length of the wetland, and water sample collection occurred once a month between August 2021 and July 2022. The results showed a neutral pH between 6 and 8 with no spatial or temporal significant differences. The mean Total Dissolved Solids (TDS) ranged between 50 – 145 mg/L. The mean nitrate concentrations (NO3-) ranged between 1.50 and 7.00 mg/L across the sampling sites. During the sampling period, a net total of 17.53 mg/L of nitrate was removed from the water column by the wetland. The mean phosphate concentration (PO43-) ranged between 0.40 – 1.40 mg/L, showing a total net removal of 2.14 mg/L during the sampling period. Coliform abundance was high closest to the wastewater treatment plant and sewage runoff and decreased along the length of the wetland, with an estimate removal of 1.17, calculated from a qualitative colour changing scoring system. E.coli bacteria was present in the wetland at all of the sampling sites between March 2022 to July 2022. This study resulted in the confirmation of a healthy, functioning wetland system where the wetland is able to reduce excess nutrients and coliform contamination. The wetland water quality shows similarities to studies conducted on wetlands in South Africa. The wetland is still under threat through possible reduced functioning as a result of excessive exposure to untreated domestic and sewage waste. A need exists for improved management and more stringent standards of water quality control from the wastewater treatment plant to reduce the risk of wetland degradation through excessive sewage exposure.
Submtted in fulfillment of the requirements for the degree Master of Science In Animal, Plant and Environmental Science in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa 2024
Keywords: Water quality monitoring; Wetland retention; Wastewater treatment plant; Faecal contamination; Chemical and biological pollutants; UCTD; SDG-8: Decent work and economic growth